1987
DOI: 10.1113/jphysiol.1987.sp016689
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the ascending limb of the sarcomere length‐tension relationship in rabbit skinned muscle fibres.

Abstract: SUMMARY1. The length dependence of Ca2+ -activated tension within the ascending limb of the length-tension relationship, corresponding to sarcomere lengths below about 2-25 ptm, was investigated in skinned fibres from rabbit psoas muscle. At high [Ca2+] a shallow phase and then a steep phase of tension decline were observed as sarcomere length was reduced, while at low [Ca2+] tension decreased monotonically with decreases in sarcomere length. The sarcomere length at which the ascending limb intersected zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
56
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 34 publications
12
56
0
Order By: Relevance
“…GREASER AND R. L. MOSS C-protein extraction has no effect on maximum shortening velocity at pCa 4-5. In our model, this result would be expected since there appear to be no long-lived crossbridges in maximally activated fibres (Allen & Moss, 1987). Thus, as shortening proceeds, normally-cycling cross-bridges would detach before straining of S-2 occurs due to the C-protein tether.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…GREASER AND R. L. MOSS C-protein extraction has no effect on maximum shortening velocity at pCa 4-5. In our model, this result would be expected since there appear to be no long-lived crossbridges in maximally activated fibres (Allen & Moss, 1987). Thus, as shortening proceeds, normally-cycling cross-bridges would detach before straining of S-2 occurs due to the C-protein tether.…”
Section: Discussionmentioning
confidence: 75%
“…The internal load may be a population of cross-bridges that detach from actin more slowly than normal, ultimately imposing a load on the muscle as it shortens. Evidence for long-lived cross-bridges during partial activation was obtained by Allen & Moss (1987) who found that stiffness was virtually unchanged and tension decreased in skinned psoas fibres when sarcomere length was shortened to a new isometric value. Slowly-cycling crossbridges have been suggested to arise in zones of transition between active and inactive functional groups on the thin filament (Moss, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…4B) and demonstrate clearly that there is very little change in stiffness as the sarcomere length decreases from 2-70 4tm to where the myosin filaments begin to collide with the Z-lines at 1 61 /sm. In a recent study, Allen & Moss (1987) also demonstrated an increase in the ratio between stiffness and tension in maximally activated skinned mammalian fibres at sarcomere lengths shorter than 1-9 ,tm. The dissociation between MgATPase activity and isometric force at short sarcomere lengths is contrary to other early observations of whole tetanized muscles (Infante et al 1964;Sandberg & Carlson, 1966) and glycerinated fibres (Hayashi & Tononura, 1968) which suggested that myofibrillar MgATPase activity decreased at short sarcomere lengths similarly to isometric force.…”
Section: General Aspectsmentioning
confidence: 84%
“…It has been suggested that changes in Ca 2ϩ sensitivity with length involve modulation of cooperative crossbridge binding to the thin filament. 27 Although sarcomere geometry and filament overlap may contribute to the availability of additional crossbridges along the ascending limb of the length-tension relationship, 28 it alone cannot account for the magnitude of the increase in force development. 3,7,29 It has been suggested that thin filament isoform proteins regulate the response to changes in length by some as of yet undetermined mechanism.…”
Section: Discussionmentioning
confidence: 99%